Antibiotic-Loaded Hydrogel for the Treatment of Lower-Limb Fracture-Related Infections: A Single Center’s Multidisciplinary Experience - Daniele De Meo; Paolo Martini; Federico Lo Torto; Flavia Petrucci; Jessica Ordonez Reyna; Vittorio Candela; Giancarlo Iaiani; Alessandra Oliva; Diego Ribuffo; Stefano Gumina (Gels)
A fracture-related infection (FRI) is a severe complication of an orthopedic trauma, often leading to challenging treatments and poor outcomes. The surgical strategies are typically categorized into one-stage or two-stage procedures, with the use of systemic and local antibiotics being crucial for infection management. This study assessed the efficacy of an antibiotic-loaded hydrogel (ALH) applied over the internal fixation devices for treating FRIs, comparing the outcomes between the one-stage (OS) and two-stage (TS) reconstructions. This retrospective study included 17 patients with an FRI treated using the ALH at a single center. The patients were divided into OS and TS reconstruction groups. The data on demographics, surgical procedures, antibiotic regimens, and outcomes were collected. The primary and secondary outcomes included the infection cure rate, bone union, complications, and reoperation rates. Among the 17 patients (mean age 48.5 years, 16 males), infections were predominantly in the tibia, with 12 chronic and 5 acute cases. Seven patients had monomicrobial infections, and nine had multidrug-resistant pathogens. No significant differences were found between the OS and TS groups in terms of the infection cure rate, bone union, or complications. One patient in the OS group experienced an infection recurrence, and bone healing was achieved in all but one case. Additional complications included delayed wound closure in two cases and implant failure in one case, requiring a reoperation. The ALH demonstrated potential as an effective local antibiotic treatment for FRIs, particularly in the one-stage reconstructions, allowing for a safe application of internal fixation devices. However, further research with larger sample sizes and longer follow-ups is needed to validate these findings.